Design thinking as an active teaching methodology in higher education: a systematic review - Alvarado, Luis Felipe (Frontiers in Education, 2025)
Design thinking stands out as a methodology that promotes creativity, user-oriented approach and interdisciplinary collaboration and has emerged as an active teaching methodology that encourages the development of practical skills and effective solving of complex problems. A documentary type research was carried out whose objective was to identify studies that explore the use of design thinking as an active methodology in higher education. Methodologically, it was approached from the principles of the PRISMA declaration, establishing as inclusion parameters research included in the period from 2014 to 2024, studies disseminated in scientific publications, studies that directly address design thinking, containing at least one of the descriptors “design thinking” or “higher education,” disseminated in Spanish or English and studies with open access format, which yielded a total of 28 documents included in the review. The findings of this review highlight the effectiveness of design thinking to improve the learning experience of students by encouraging their active participation, critical thinking and interdisciplinary collaboration.